Eradication of the fungus Epichloë coenophiala from Schedonorus arundinaceus (tall fescue) seeds by interrupting the vertical transmission process - Petigrosso, Lucas R. (2019)
Fil: Petigrosso, Lucas R. Universidad Nacional de Mar del Plata. Facultad de Ciencias Agrarias. Balcarce, Argentina.